h - Bernstein, Daniel J.; Chatterjee, Sanjit; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 12th International Conference on Cryptology in India, INDOCRYPT 2011, held in Chennai, India, in December 2011. The 22 revised full papers presented together with the abstracts of 3 invited talks and 3 tutorials were carefully reviewed and selected from 127 submissions. The papers are organized in topical sections on side-channel attacks, secret-key cryptography, hash functions, pairings, and protocols.
Keywords: Computer science; Computer Communication Networks; Data protection; Data encryption (Computer science).; Computer software; Computational complexity; Information Systems; Computer Science; Data Encryption; Computer Communication Networks; Algorithm Analysis and Problem Complexity; Management of Computing and Information Systems; Systems and Data Security; Discrete Mathematics in Computer Science